Legal Bases For The Exercise Of Universal Jurisdiction In Terms Of War Crimes - خالقي أبو الفتح; فتحي مرتضى; شربو نور الدين (Latakia University Journal - Economic and Legal Sciences Series, 2022)
When considering war crimes committed abroad, national courts rely on the principle of universal jurisdiction. The importance of this principle stems from the fact that it represents a legal tool in the hands of the state that gives it jurisdiction to prosecute and punish international criminals, regardless of the existence of a traditional link between the state of the place of arrest of the accused and the crime committed. Thus, the ultimate goal of international criminal law is reached, that is, the impunity of criminals and the protection of the interests of the international community. Granting internal courts universal jurisdiction over war crimes came as a result of multiple legal bases contained in international agreements and resolutions, which gives the national government the necessary legitimacy and makes it an argument against all. Therefore, studying those international provisions and decisions will lead to an accurate identification of the limits of the principle of war crimes. International jurisdiction and removes ambiguity from it, which contributes to the development of internal penal legislation.